Climate change response: Linking research, policy and action. (December 2014) - Troy, Patrick
We are now close to reaching what climate scientists advise is a 'tipping point' when the injuries we have visited on the planet will become self-reinforcing and produce an ecosystem that is alien to human life. The mal-distribution of consumption within and between nations is a major reason why there is little agreement on appropriate remedial action. Ensuring planetary survival while reducing inequity is made the more difficult, because the richest one-seventh of the world's population has already reached consumption levels beyond the capacity of the planetary ecosystem to accommodate it.